A Rare Case of Traumatic Bilateral Sixth Cranial Nerve Palsy - BB, Hamidon; HS, Md Shariful; MZ, Nasaruddin (IIUM Medical Journal Malaysia, 2012)
Traumatic bilateral sixth cranial nerve palsy is a rare condition which is typically associated with additional intracranial, skull, and cervical spine injuries. We describe a case of complete bilateral sixth nerve palsy in a 28-year-old female patient after an alleged motor vehicle accident. She had altered level of consciousness but no intracranial lesion or associated skull or cervical spine fracture was detected. In this case, we discussed the differential diagnoses, initial workup, and possible treatment options in cases of traumatic 6th nerve palsy.